The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1111/j.1467-9841.2006.00296.x
|View full text |Cite
|
Sign up to set email alerts
|

Indexing stance: Reported speech as an interactional evidential1

Abstract: The notion of linguistic stance as a non-grammaticalized form of evidentiality is here explored through an investigation of reported speech in English interaction. Reported speech is found to be one of a variety of resources with which speakers lay claim to epistemic priority vis-à-vis recipients. Such resources are not identifiable as stance markers independently of the sequential contexts in which they appear; sequential position is shown to be central in providing at once a constraint on what can be said an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0
9

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(106 citation statements)
references
References 54 publications
(58 reference statements)
4
93
0
9
Order By: Relevance
“…most of the previous CA work into the negotiation of epistemics has focussed on first and second assessment sequences (e.g. Heritage and raymond 2005;raymond and Heritage 2006;Clift 2006) and question-answer sequences (e.g. Heritage and raymond 2010;Heritage 2010;raymond 2010).…”
Section: Discussionmentioning
confidence: 99%
“…most of the previous CA work into the negotiation of epistemics has focussed on first and second assessment sequences (e.g. Heritage and raymond 2005;raymond and Heritage 2006;Clift 2006) and question-answer sequences (e.g. Heritage and raymond 2010;Heritage 2010;raymond 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Holt (1996: 230) argues that reports of speech lend the speaker 'an air of objectivity', demonstrating that the position is one held by more than one person (if the reporting and reported speakers are different people) and that the view being expressed is one formulated over time. Related to this, Couper-Kuhlen (2007: 119) argues that reported discourse supports an assessment by 'adding strategic detail and attesting to its historicity', and Clift (2006Clift ( , 2007 found that in arguments over epistemic rights to assess reported discourse is 'one of the most powerful evidential displays of having got there first ' (2007: 149). Wooffitt (2007: 245) makes a similar point, arguing that the 'authenticity of a claim or the authority of a speaker can be established and defended' through use of reported discourse, while Leudar and Antaki (1996: 24) state that to 'report talk is to offer some kind of guarantee of its authenticity'.…”
Section: Functions Of Reported Discoursementioning
confidence: 99%
“…The ability of quoted utterances to confer authority for a given claim stems from the relationship between the source of the quoted utterance and the content of the quoted utterance. To the degree that the quoted party is recognized by the participants in an interaction as having authority with respect to the claim expressed in the quoted utterance, or to the degree to which the quoted utterance demonstrates authority by indexing the quoted party's participation in a relevant event (Clift 2006), the quoted utterance can function as an 'authoritative' means for the speaker to introduce a relevant claim into the ongoing interaction. Given the analysis of distancing as a conversational implicature, the fact that speakers can draw on the authority associated with particular pairings of quoted parties and quoted utterances is not surprising, as implicatures of non-commitment to the utterance are simply defeased by the authority of the quoted utterance.…”
Section: Cqf and The Pragmatics Of Quotationmentioning
confidence: 99%